Generation X's Understanding of and Adherence to Covid-19 Prevention Protocol in Religious Activities - Indri Ramayanti; Thia Prameswarie; Ahmad Ghiffari; Dientya Nur Anggina; Rista Silvana; Siska Fitriani (Jurnal Ilmiah Kesehatan (JIKA), 2023)
The Coronavirus disease 2019 (Covid-19) pandemic has become a serious global health problem, control its spread through knowledge that can influence people's behavior and compliance with certain rules knowledge can help prevent the spread of Covid-19. This study aimed to determine the relationship between Generation X's knowledge of Covid-19 with their compliance with the protocol of mask-wearing, physical distancing, and hand washing in religious activities. This research was analytical observational research with a cross-sectional design. The research population was Generation X, who carried out religious activities at houses of worship in Palembang. Individuals born between 1965 and 1980 met the criteria for Generation X in this study. The sample was collected using the cluster random sampling method, yielding 147 samples. A google forms questionnaire and structured interviews are used for primary data collection. The results showed that as many as 80 (54,4%) subjects had good knowledge of Covid-19, while 67 (45,6%) did not. Regarding the level of compliance, 90 (6,2%) complied with the instruction of mask-wearing, 57 (38,8%) did not, 79 (53,7%) obeyed the protocol of physical distancing and hand-washing, while 68 (46,3%) did not. This finding revealed a relationship between the level of knowledge and compliance with the instruction of wearing masks, physical distancing, and washing hands in doing religious activities in houses of worship in Palembang City to prevent Covid-19, with a p-value=0,00. However, preventing and monitoring the termination of the Covid-19 pandemic must continue to be carried out by various parties.